Dynamic Efficiency of Product Market Competition - Jeroen Hinloopen; Jan Vandekerckhove (Tinbergen Institute, 2007)
We consider the efficiency of Cournot and Bertrand equilibria in a duopoly with substitutable goods where firms invest in process R&D. Under Cournot competition firms always invest more in R&D than under Bertrand competition. More importantly, Cournot competition yields lower prices than Bertrand competition when the R&D production process is efficient, when spillovers are substantial, and when goods are not too differentiated. The range of cases for which total surplus under Cournot competition exceeds that under Bertrand competition is even larger as competition over quantities always yields the largest producers' surplus.
Keywords: L13; 330; Bertrand competition; Cournot competition; process R&D; efficiency; Wettbewerb; Duopol; Technischer Fortschritt; Spillover-Effekt; Theorie